High‐Resolution 3D Marine Seismic Investigation of Hedeby Harbour, Germany. (21st January 2013) - Mueller, Christof; Woelz, Susanne; Kalmring, Sven
Abstract : Offshore 3D‐seismic acquisition has been a standard for high‐precision structural imaging in the oil and gas industry for many years. Recently this technique has been adapted by only a few teams to the resolution required for archaeological marine investigation. In contrast to sonar techniques, the 3D‐seismic method produces images below the sea‐floor. We investigate the harbour of the Viking age proto‐town of Hedeby in Northern Germany with the SEAMAP‐3D system. SEAMAP‐3D allows for rapid acquisition and employs an automated data processing sequence. We observe a wealth of archaeologically relevant detail and compare our results with previous work.